Cytogenetic characterization of Partamona cupira (Hymenoptera, Apidae) by fluorochromes - Jefferson de Brito Marthe; Silvia das Graças Pompolo; Lucio Antônio de Oliveira Campos; Tânia Maria Fernandes Salomão; Mara Garcia Tavares (Genetics and Molecular Biology, 2010)
Four colonies of the stingless bee Partamona cupira (Hymenoptera: Apidae) were cytogenetically analyzed using conventional staining and the fluorochromes CMA3 e DAPI. The females have 2n = 34 chromosomes (2K=32 +2 ). Some females, however, presented an additional large B acrocentric chromosome, to a total of 2n = 35. Chromosome B and the chromosomal pairs 2, 9 and 10 showed CMA3+ bands, indicating an excess of CG base-pairs. A clear association was verified between the P. helleri B chromosome SCAR marker and the presence of a B chromosome in P. cupira. The data obtained suggests that B chromosomes in P. helleri and P. cupira share a common origin.